Gestational Trophoblastic Disease - Deep, JP; Sedhai, LB; Napit, J; Pariyar, J (Journal of Chitwan Medical College, 2013)
Gestational trophoblastic disease (GTD) is a group of tumors that arise from placental tissue and secrete β-hCG. GTD is a combination of benign or invasive mole and malignant known as Gestational Trophoblastic Neoplasia (GTN). Prevalence, diagnosis and treatment of GTD have drastically changed in recent years. DOI: http://dx.doi.org/10.3126/jcmc.v3i2.8434 Journal of Chitwan Medical College Vol.3(2) 2013 4-11